IMPLEMENTASI METODE SUZUKI DALAM PEMBELAJARAN BIOLA TINGKAT DASAR DI ERA MUSIKA MEDAN - Bernadetta, Arga Novia (Universitas Negeri Medan, 2018)
This study aims to describe the implementation of basic level violin learningusing the Suzuki method in the Medan Musika Era. The subjects in this study were students who tookviolin instruments in the Medan Musika Era. This study focused on the problems associated with theimplementation of basic level violin learning with the Suzuki method, which was viewed from theprocess of the steps of the study. This study used descriptive qualitative research methods, namelya research method that aims to describe in detail and clearly about a phenomenon which is the focusof research. The results of the research on the implementation of basic level violin learning usingthe Suzuki method in the Medan Musika Era show as follows (1) Education 'starts at a very earlyage by not limiting students who learn violin in the Musika Era. (2) Prioritizing to teach students tolisten to just play a musical instrument, by the way the teacher demonstrates the song learned by thenew student, the student mimics the song. (3) Violin learning takes place by giving songs that are inSuzuki's books repeatedly. (4) Learning to read beam notation using fingering in accordance withwhat is in the Suzuki method book.